The origin of bacterial contamination in AL-Habania reservoir in Iraq (Baghdad Science Journal, 2011)
Bacterial contamination of AL-Habania reservoir was studied during the period from February 2005 to January 2006; samples were collected from four stations (AL-Warrar, AL-Theban regulator, middle of the reservoir and the fourth was towards AL-Razzaza reservoir). Coliform bacteria, faecal Coliforms, Streptococci, and faecal Streptococci were used as parameters of bacterial contamination in waters through calculating the most probable number.Highest count of Coliform bacteria (1500 cell/100ml) was recorded at AL-Razaza during August, and the lowest count was less than (300 cell/100ml) in the rest of the collection stations for all months. Fecal Coliform bacteria ranged between less than 300 cells/100ml in all stations for all months to 700 cell/100ml in AL-Warrar, AL-Razaza and in the middle of the reservoir stations during August. Streptococci bacteria count ranged between less than 300 cell/100ml to 700 cell/100ml as a highest record in AL-Razaza station during August for both.The ratio between fecal coliforms and fecal streptococci (FC: FS) was detected to determined the origin of the pollution in the reservoir depending on Geldrich statistical law in this research, the ratio ranged between (1) to (2.3).